Dynamics of Gender Self and Other in Sharon Doubiago’s South America Mi Hija - Kurraz, Abdullah H. (American International Journal of Social Science Research, 2020)
This paper explores the poetic feminist discourse of the South American poet Sharon Doubiago’s epic South America Mi Hija and how she engenders and maintains her gender’s visions and beliefs in masculine societies that still engulf the whole human world. She poetically defends herself and her gender refusing to submit to the standing patriarchal paradigm. She portrays herself as a modern spokesperson of her gender and its vulnerability to victimization. Doubiago also tries to cast her challenge against the dominant patriarchal power. Further, this paper sheds light on the poet’s optimism in winning the battle in the light of modern feminist analysis, providing relevant representations of her poetic discourse. It elucidates how the poet publicizes her feminist and gender thoughts despite the domination of the masculine power. As a result, as an intimate feminist poet, Doubiago succeeds in identification with her psyche and other similar selves that can assimilate with her soul and vision. In a broader sense, the focal hypothesis of this paper revolves around conceptualizing feminist poetics and gender in an appreciative receptionist way.